Analysing the project delay causes and improving quality using multi-project strategies - Nur Amirah Syahirah, Azman; Faizir, Ramlie; Wan Zuki Azman, Wan Muhamad; Mohd Yazid, Abu; Nolia, Harudin (Penerbit Akademia Baru, 2024)
Numerous reasons for project delays from the viewpoints of the client and the contractor have only been somewhat studied. The aim of this paper is to recognize the delays' underlying causes and issues ways to reduce them considering the progress of the project. Consequently, 106 contractor-side experts and 82 client-side experts in project management were the subjects of this study. The clients and contractors gave the same importance to factors like poor communications and governmental approvals in projects that were successful (had a time delay of less than 10%). Similar mitigating techniques including rigorous project monitoring, skill development training, and effective logistics planning were advised. When projects were unsuccessful (with a time delay of more than 10%), they displayed a wide range of behaviours.